2021
DOI: 10.1099/ijsem.0.005032
|View full text |Cite
|
Sign up to set email alerts
|

Pseudonocardia abyssalis sp. nov. and Pseudonocardia oceani sp. nov., two novel actinomycetes isolated from the deep Southern Ocean

Abstract: The actinomycetes strains KRD168T and KRD185T were isolated from sediments collected from the deep Southern Ocean and, in this work, they are described as representing two novel species of the genus Pseudonocardia through a polyphasic approach. Despite sharing >99 % 16S rRNA gene sequence similarity with other members of the genus, comparative genomic analysis allowed species delimitation based on average nucleotide iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As a model of free‐living Pseudonocardia , the whole‐genome sequence of three species ( Pseudonocardia abyssalis KRD168, Pseudonocardia oceani KRD185 and Pseudonocardia sp. KRD291) isolated previously from the deep Southern Ocean (Millán‐Aguiñaga et al, 2019; Parra et al, 2021) was selected and compared with Pseudonocardia strains from diverse ecological and geographical origins (Table S1). These strains correspond to two phylogenetically closely related species ( P. abyssalis and P. oceani ), and a third species ( Pseudonocardia KRD291), which is phylogenetically closely related to Pseudonocardia sediminis , another species of marine origin.…”
Section: Resultsmentioning
confidence: 99%
“…As a model of free‐living Pseudonocardia , the whole‐genome sequence of three species ( Pseudonocardia abyssalis KRD168, Pseudonocardia oceani KRD185 and Pseudonocardia sp. KRD291) isolated previously from the deep Southern Ocean (Millán‐Aguiñaga et al, 2019; Parra et al, 2021) was selected and compared with Pseudonocardia strains from diverse ecological and geographical origins (Table S1). These strains correspond to two phylogenetically closely related species ( P. abyssalis and P. oceani ), and a third species ( Pseudonocardia KRD291), which is phylogenetically closely related to Pseudonocardia sediminis , another species of marine origin.…”
Section: Resultsmentioning
confidence: 99%
“…Certain strains that were considered during our phylogenetic analyses based on 16S rRNA gene sequences were omitted from the aforementioned investigations because of the unavailability of their protein sequences in the NCBI database [22]. Hence, despite the high sequence similarity (99.56 %) observed in the 16S rRNA gene between strain I65 T and N. yanshanensis CCBAU 05354 T , the whole-genome sequence analysis indicates that strain I65 T and N. yanshanensis CCBAU 05354 T represent two distinct novel species [23]. Additionally, our genomic analysis using the NCBI databases, Uniprot blast , and the dfast web-based tool revealed that only the genome of strain I65 T possesses heavy metal resistance genes, such as cusA , cusB , and merA () [24].…”
Section: Genomic Featuresmentioning
confidence: 99%
“…Many Streptomyces species can be readily isolated from any soil, but less well studied genera of filamentous actinobacteria such as Amycolatopsis , Pseudonocardia , Saccharopolyspora , and Salinispora are often described as rare because they are recovered less frequently. Pseudonocardia species, for example, are slow-growing and difficult to culture, and have been most commonly found living in a mutually-beneficial symbiosis with attine ants in South and Central America but they have also been isolated from soil and deep-sea marine sediments, suggesting a combination of free-living and symbiotic species in this genus [23–28]. The marine environment is the natural niche of Salinispora species, which have been described as the ‘ Streptomyces of the sea’ because they are also prolific producers of SMs including molecules currently undergoing clinical trials [24].…”
Section: A Brief Introduction To the Actinobacteriamentioning
confidence: 99%